Cognitive processes and math performance: a study with children at third grade of basic education - Campos, I. S.; Almeida, L. S.; Ferreira, A. I.; Martinez, L. F.; Ramalho, G. (European Journal of Psychology of Education, 2013)
The present study aims to examine the relationship between cognitive factors and mathematical achievement in primary education. Participants were 103 Portuguese third grade students, aged 8 and 9. All participants completed a battery for working memory (WMTB-C), a test of general intelligence (Raven's Progressive Color Matrices), a selective attention test (d2), and mathematical exercises (arithmetic story problems and measurement skills). Data suggested significant correlations between math performance, executive, visuospatial sketchpad and g factor. Our findings suggest the importance of the cognitive factors in two mathematical domains considered. In consonance with the research in this area, we conclude that working memory (WM) assumes an important role in different math curricular achievements.